1992
DOI: 10.1128/iai.60.5.2092-2095.1992
|View full text |Cite
|
Sign up to set email alerts
|

Enteroaggregative Escherichia coli strains secrete a heat-labile toxin antigenically related to E. coli hemolysin

Abstract: A protein toxin of approximately 120,000 Da secreted by nonhemolytic enteroaggregative Escherichia coli strains cross-reacted in Western blots (immunoblots) with antibodies raised against the C-terminal region ofE. coli hemolysin. Treatment of HEp-2 cells with enteroaggregative E. coli or culture supernatants caused elevation of intracellular calcium and stimulated calcium-dependent protein phosphorylation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
1

Year Published

1994
1994
2010
2010

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(29 citation statements)
references
References 28 publications
(15 reference statements)
1
27
1
Order By: Relevance
“…It has recently been demonstrated that EAggEC elaborate a low molecular mass partially heat-stable enterotoxin which induces ion transport alterations consistent with a secretory response [3]. A heat-labile toxin antigenically related to E. coli hemolysin which could promote cellular changes in vitro and these changes may be important factors in the development of diarrhoea in vivo has also been documented [4]. The association of one or both of these factors in the pathogenesis of EAggEC mediated secretory diarrhoea seems likely because none of the 21 strains recovered in this study produced any of the conventional heat-labile, heat-stable or vero toxins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has recently been demonstrated that EAggEC elaborate a low molecular mass partially heat-stable enterotoxin which induces ion transport alterations consistent with a secretory response [3]. A heat-labile toxin antigenically related to E. coli hemolysin which could promote cellular changes in vitro and these changes may be important factors in the development of diarrhoea in vivo has also been documented [4]. The association of one or both of these factors in the pathogenesis of EAggEC mediated secretory diarrhoea seems likely because none of the 21 strains recovered in this study produced any of the conventional heat-labile, heat-stable or vero toxins.…”
Section: Discussionmentioning
confidence: 99%
“…Though the exact mechanism of pathogenesis of EAggEC is unknown, preliminary insights have been gained by electron microscopic and pathophysiological studies which suggests that EAggEC may be a large-bowel pathogen which colonize by a fimbrially mediated adhesion mechanism. EAggEC have been documented to elaborate a heat-stable enterotoxin [3] and a heat-labile toxin antigenically related to E. coli hemolysin [4]. EAggEC are characterized by their typical mannose resistant 'stacked-brick' like lattice pattern of adherence to HeLa and HEp-2 cells in tissue culture [1].…”
Section: Introductionmentioning
confidence: 99%
“…The toxin also reacts with sera from children and adults with natural or experimental EAggEC infection (Eslava et al 1993;. Baldwin et al (1992) showed that EAggEC secrete a protein of MW 120 kDa that shares epitopes with the C-terminal region of E. coli a-haemolysin. When cell cultures were exposed to EAggEC supernatant fluids containing the haemolysin protein, concentrations of intracellular calcium were raised, stimulating calcium-dependent protein phosphorylation.…”
Section: Toxin Production By Eaggecmentioning
confidence: 99%
“…Paul et al (1994) suggested that diarrhoea due to EAggEC is secretory and the symptoms seen in volunteers and in epidemiological studies would support this. Both EAST 1, haemolysin and 108 kDa protein can cause secretion by distinct mechanisms (Baldwin et al 1992;Eslava et al 1993;Savarino et al 1993). EAST 1 is only produced by approximately half of the E. coli isolates showing the EAggEC phenotype.…”
Section: Eaggec Heat-stable Enterotoxin (East 1)mentioning
confidence: 99%
“…A novel enteroaggregative E. coli heat-stable enterotoxin, EAST 1, is also encoded by genes located on this virulence plasmid [ll]. Enteroaggregative E. coli also produce a hemolysin-like toxin [12]. Finally, it has recently been reported that enteroaggregative E. coli express a 108-kDa protein, distinct from other moieties, that is responsible for potent cytotoxic activity [13], perhaps explaining the destructive histopathologic lesions observed in the original animal models of enteroaggregative E. coli infection [9].…”
mentioning
confidence: 99%